Legal Analysis of Unauthorized Waste Dumping by Companies - Indriyati, Siti Nuraynul; Rosnawati , Emy (Rechtsidee, 2024)
General Background: Environmental degradation due to human activities has led to significant ecological issues, necessitating robust legal frameworks for environmental preservation and management. Specific Background: In Indonesia, Law Number 32 of 2009 addresses these concerns, highlighting the need for legal regulations to mitigate environmental harm. Knowledge Gap: Despite the existence of such laws, there is a lack of comprehensive understanding regarding the effectiveness and implementation of regulations specifically related to the criminal act of dumping waste by companies. Aims: This research aims to analyze the legal regulations governing the criminal act of waste dumping in environmental media without permission, with a focus on normative legal research methodology. Results: The study reveals that, according to Law No. 32 of 2009 and provincial regulations on waste management, several regencies or cities have established legal frameworks to address this environmental crime, while at least five provinces still lack sufficient regulations. Novelty: This research provides a detailed examination of the regulatory landscape, identifying gaps and inconsistencies in the enforcement of environmental laws across different regions in Indonesia. Implications: The findings underscore the necessity for a more harmonized and stringent regulatory approach at both the provincial and national levels to ensure effective environmental protection and compliance by companies. This study contributes to the existing body of knowledge by offering insights into the legislative and enforcement challenges in environmental law, particularly in the context of criminal activities related to waste management. Highlights: Legal Framework: Examines the effectiveness of Law No. 32 of 2009 and provincial regulations on waste dumping. Regional Disparities: Identifies gaps in regulatory enforcement across different provinces. Normative Research: Emphasizes the use of laws and regulations as primary sources for analysis. Keywords: Legal Arrangements, Waste Dumping, Criminal Acts